PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI PENGUKURAN SATUAN BERAT SISWA KELAS III SD NEGERI BANDUNGAN 01 - Martafuri Damayanti; Waskito Aji; Muhammad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to test the effectiveness og the Problem Based Learning (PBL) model in improving mathematics learning outcomes in weight unit measurement material for class III student at SD Negeri Bandungan 01. The main problem in this research is the low student learning outcomes due to the use of lecture methods that are less innovative and do not involve maximum student activity. The research method uses a quantitative approach with a One Group Pretest-Posttest design for 18 students. Data was collected throught problem solving tests and analyzed using the Paired Sample T-Test. The results showed a significant increase in the average score, from 46,11 on the pretest to 85,83 on the posttest. Statistically Ha accepted. It was concluded that the application of the PBL model was effective in improving student learning outcomes trought the use of real world problems which made learning more contextual and meaningful.